Apples versus brownies: A field experiment in rearranging conference snacking buffets to reduce short-term energy intake. Issue 1 (1st January 2016) - Hansen, Pelle Guldborg; Skov, Laurits Rohden; Jespersen, Andreas Maaløe; Skov, Katrine Lund; Schmidt, Karsten
ABSTRACT: More and more people eat out and, therefore, foodservice business has an increasing influence on people's dietary intake. Foodservice business should, first and foremost, deliver a nice tasting meal of high quality—but health should not be neglected. Nudging and choice architecture is a field of foodservice business research that is gaining interest and this article offers original research in this field.